Penguatan Konsep Elektrolisis melalui Praktikum Interaktif pada Kelas XII A di SMAN I Suwawa - Thayban, Thayban; Kurniawati, Erga; Munandar, Haris; Sangkota, Vivi Dia Afrianti (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The purpose of this community service activity is to strengthen the concept of electrolysis for students of SMAN 1 Suwawa through interactive laboratory exercises, as well as to enhance students' understanding and practical skills related to the electrolysis process. The partners involved in this activity include the Principal, Chemistry Teacher, and all 12th-grade students of SMAN 1 Suwawa. The implementation method of the activity involves four main stages: a pre-test to measure initial understanding, providing material to reinforce the concept of electrolysis, conducting interactive laboratory exercises using electroplating tools, and a post-test to measure the improvement in students' understanding. The results of this activity show a significant improvement in the understanding of electrolysis concepts, with an N-Gain value of 76.8%, indicating the effectiveness of this method in improving students' learning outcomes. Based on these findings, it is recommended to continue applying interactive laboratory approaches in science education in secondary schools, as well as utilizing technology and interactive modules to support students' understanding of complex chemical concepts. Additionally, teacher training is also important to ensure the sustainability of effective laboratory-based learning.